Industrial waste acid cooperatively modified red mud-based denitration catalyst, preparation method and application thereof

CN122999221APending Publication Date: 2026-10-30CHONGQING THREE GORGES UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611100599.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]专利CN104801349A公开了一种V2O5-WO3/TiO2体系NH3-SCR脱硝催化剂及其制备方法,该技术脱硝效率较高,但活性组分成本高且抗中毒性能不足;专利CN202110281930.9公开了一种赤泥基NH3-SCR催化剂的制备方法,通过酸处理后负载CeO2助剂来提升活性,但所制催化剂颗粒较大,需经超声细化处理,工艺复杂且催化性能仍有待提升

Benefits of technology

1)双废协同深度资源化,实现“变废为宝”的价值跃升 本发明利用钛白废酸、电镀废酸等工业废酸对赤泥进行改性,不仅消纳了赤泥和废酸两种大宗固废,更创新性地挖掘了废酸中伴生金属离子(如钛、铬、锌等)的潜在价值。本发明将传统工艺中需去除的“杂质离子”转化为“原位掺杂协同助剂”,实现了从简单的“以废治废”到“高值化协同利用”的技术跨越,环境效益与经济效益显著

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999221A_ABST
    Figure CN122999221A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of industrial flue gas pollution control and solid waste resource utilization, and particularly relates to an industrial waste acid synergistically modified red mud-based denitration catalyst as well as a preparation method and application thereof, wherein the red mud-based denitration catalyst is prepared by synergistic modification of red mud and industrial waste acid; the red mud is a catalyst base material, and the industrial waste acid is a structure regulating component for regulating the surface acid-base properties and pore structure of the red mud; in the red mud-based denitration catalyst, the mass fraction of iron element is 10.4% to 13.6%, and the mass fraction of sulfur element is greater than 0 and not more than 26%. The present application takes industrial titanium dioxide waste sulfuric acid and alumina industrial red mud as main raw materials, and prepares the red mud-based denitration catalyst under mild conditions through a waste acid synergistic modification process, aiming to realize efficient removal of NO x from industrial fixed source flue gas and long-term stable operation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of industrial flue gas pollution control and solid waste resource utilization technology, specifically to an industrial waste acid synergistic modification red mud-based denitrification catalyst, its preparation method, and its application. Background Technology

[0002] Nitrogen oxides (NO) x NOx is one of the major pollutants in industrial stationary source flue gas, widely originating from combustion and process technologies in industries such as coal-fired power plants, iron and steel metallurgy, waste incineration, and chemical production. It is not only a significant precursor to photochemical smog and fine particulate matter, but also poses a serious threat to the ecological environment and human health. Therefore, achieving NOx control in industrial flue gas is crucial. x The efficient removal of NO has become an important research direction in the field of air pollution control. Currently, industrial flue gas denitrification technology mainly uses ammonia selective catalytic reduction (NH3-SCR), and commercial catalytic systems represented by V2O5-WO3 / TiO2 have achieved relatively mature engineering applications. However, this system still suffers from problems such as high cost of active components, easy catalyst poisoning and deactivation, and insufficient adaptability to complex flue gas conditions. Furthermore, although some adsorption / catalytic materials possess certain NO removal capabilities... x While possessing high removal capacity, these materials generally suffer from limitations such as limited reactivity, poor stability, and difficulty in large-scale application. Therefore, there is an urgent need to develop novel denitrification materials that combine low cost, high activity, and strong adaptability to various operating conditions.

[0003] The production of titanium dioxide (TiO2) generates a large amount of industrial waste acid (typically with a sulfuric acid concentration of about 20%) as a byproduct. Direct discharge without proper treatment not only results in a serious waste of sulfur resources but also poses environmental risks such as water and soil acidification. Meanwhile, the large amounts of red mud generated from the alumina industry, due to its high alkali content, strong cementing properties, and low comprehensive utilization rate, not only occupy significant amounts of land but also pose potential ecological hazards such as alkali pollution and heavy metal migration when stored for extended periods. Current processes often employ independent disposal routes for these two types of industrial waste, which generally suffer from lengthy processes, high operating costs, and low resource utilization efficiency, making it difficult to simultaneously achieve large-scale disposal and high-value utilization. Given that the red mud dealkali removal process requires a large amount of acidic media, and the waste sulfuric acid from titanium dioxide can provide the necessary acidic environment, while also providing abundant surface acidic sites for red mud, the preparation of denitrification catalysts by co-modifying red mud with industrial waste acid can not only achieve the reduction and high-value utilization of both types of industrial solid waste, but also effectively reduce the alkalinity of red mud and release valuable metal active components through the acidic environment, thus opening up new technical pathways for the synergistic treatment and efficient recycling of industrial solid waste.

[0004] Patent CN104801349A discloses a V2O5-WO3 / TiO2 system NH3-SCR denitrification catalyst and its preparation method. This technology has high denitrification efficiency, but the active component is costly and has insufficient resistance to poisoning. Patent CN202110281930.9 discloses a method for preparing a red mud-based NH3-SCR catalyst, which improves activity by loading CeO2 as an additive after acid treatment. However, the prepared catalyst particles are large and require ultrasonic refining, making the process complex and the catalytic performance still needs improvement. In addition, existing technologies for preparing flue gas purification materials from solid waste resources have also been reported, but they generally suffer from problems such as complex modification processes, limited performance improvement, and insufficient industrial adaptability, making it difficult to achieve a coordinated balance between low cost, high activity, and large-scale application. Summary of the Invention

[0005] The purpose of this invention is to provide an industrial waste acid-co-modified red mud-based denitrification catalyst, its preparation method, and its application. Using industrial titanium dioxide waste sulfuric acid and alumina industrial red mud as main raw materials, the red mud-based denitrification catalyst is prepared under mild conditions through a waste acid-co-modification process, aiming to reduce NO in industrial stationary source flue gas. x Highly efficient removal and long-term stable operation.

[0006] To achieve the above objectives, the technical solution specifically adopted by the present invention is as follows: A red mud-based denitrification catalyst synergistically modified with industrial waste acid. This catalyst uses solid waste red mud as the carrier matrix, abandons the traditional preparation system of precious metals and high-purity chemical raw materials, and innovatively utilizes the metal ions associated with industrial waste acid (such as titanium ions in titanium dioxide waste acid and chromium / zinc ions in electroplating waste acid) as in-situ doping synergists.

[0007] By using waste acid as a modification and control medium, and through the synergistic mechanism of "acid washing and etching - in-situ doping", the micro-pore structure of red mud is reconstructed through proton exchange, transforming the original dense layered structure of red mud into a high specific surface area mesoporous-macroporous hierarchical structure, exposing more active sites. On the other hand, the residual metal ions in the waste acid are used to conduct heterogeneous atomic doping and lattice substitution with iron and aluminum species on the surface of red mud, thereby adjusting the Lewis acid / Brønsted acid ratio on the catalyst surface and optimizing the surface redox capability.

[0008] After co-modification with waste acid, the catalyst exhibits precisely controlled content of iron and sulfur active components, as well as in-situ doped synergistic agents. The iron mass fraction is stably controlled between 10.4% and 13.6%, the sulfur mass fraction is strictly controlled to be greater than 0 and not exceeding 26%, and the in-situ doped synergistic agent mass fraction is 0.1% to 2.5%. This unique composition creates abundant Fe-OSM (M being associated metals in the waste acid) multi-element active centers on the catalyst surface, significantly enhancing the catalyst's NO adsorption and activation capacity, as well as its sulfur and water resistance, ensuring stable and efficient denitrification capabilities.

[0009] This invention also discloses a method for preparing the above-mentioned industrial waste acid synergistic modification red mud-based denitrification catalyst. The entire process is simple, the conditions are controllable, and it is environmentally friendly, making it suitable for industrial-scale mass production. The specific preparation process is as follows: Industrial waste acid of a specific concentration is selected and mixed with red mud according to a predetermined solid-liquid ratio. During the acid washing and modification reaction, the reaction system is controlled to be in a dynamic stirring state. Hydrogen ions in the waste acid selectively dissolve inert components such as sodium and silicon in the red mud lattice, while inducing polyvalent metal cations in the waste acid to migrate to and anchor on the surface of the red mud, forming an integrated "etching-reconstruction-doping" modification process.

[0010] After structural modification, waste acid is recovered through solid-liquid separation. The recovered waste acid can be recycled multiple times, significantly reducing production costs. The separated solid material is dried to remove water and then subjected to segmented high-temperature calcination crystallization treatment. The calcination process not only removes surface adsorbed water but also promotes the transformation of amorphous iron species on the surface into the highly active α-Fe2O3 crystalline phase, forming a solid solution structure with doped heterogeneous metal ions, further enhancing the fluidity of lattice oxygen. Finally, a modified red mud-based denitrification catalyst is obtained.

[0011] Furthermore, the present invention specifies the preparation process as follows: The industrial waste acid mass fraction is controlled at 10–40 wt%, the solid-liquid ratio of waste acid to red mud is 2–6 mL / g, the acid washing modification temperature range is 20–130 °C, and the reaction time is 0.5–6 h. The waste acid is recycled 5–10 times. During the recycling process, the concentration of polyvalent metal cations enriched in the waste acid gradually increases, which in turn enhances the content of in-situ doping synergists in subsequent batches of catalyst, thereby improving the surface acidity and redox performance of the catalyst and realizing the tiered utilization of waste acid value. The calcination temperature is controlled at 300–700 °C, preferably using programmed temperature rise calcination (heating rate 2–5 °C / min) to induce the directional growth of mesoporous structures. All parameters are coordinated to ensure the optimal state of the catalyst microstructure and active components.

[0012] This invention discloses the industrial application scenarios of the above-mentioned catalyst. This catalyst can be widely used in industrial flue gas denitrification treatment, and exhibits excellent stability, especially under complex flue gas conditions characterized by high sulfur and high dust.

[0013] Suitable for conventional and complex flue gas denitrification conditions: NO volume fraction 300–1000 ppm, NH3 to NO molar ratio 0.8–1.2, O2 volume fraction 1%–10%, SO2 volume fraction 0–200 ppm, H2O volume fraction 0–10%, mass hourly space velocity 10000–60000 mL•g - ¹•h - ¹, The reaction temperature is 250–500 ℃. It has wide adaptability to operating conditions and strong denitrification stability, solving the technical problem of easy sulfation and deactivation of traditional red mud-based catalysts.

[0014] This invention has the following characteristics and beneficial effects: 1) Deep Resource Utilization of Waste and Waste: Achieving a Value Leap from Waste to Treasure. This invention utilizes industrial waste acids such as titanium dioxide waste acid and electroplating waste acid to modify red mud. This not only eliminates two major solid wastes—red mud and waste acid—but also innovatively taps into the potential value of associated metal ions (such as titanium, chromium, and zinc) in the waste acid. This invention transforms the "impurity ions" that need to be removed in traditional processes into "in-situ doping synergistic agents," achieving a technological leap from simple "waste treatment" to "high-value synergistic utilization," resulting in significant environmental and economic benefits. 2) Constructing a dual modification mechanism of "etching-doping," synergistic optimization of microstructure and active components. Unlike traditional single acid washing, which can only remove alkaline impurities, this invention utilizes a synergistic mechanism of "acid washing and etching-in-situ doping." On one hand, it uses proton exchange to dissolve inert components, constructing a mesoporous-macroporous hierarchical pore structure, significantly increasing the specific surface area. On the other hand, it induces multivalent metal cations in waste acid to anchor in-situ to the red mud lattice, forming "Fe-OSM" multi-element active centers. This unique microstructure not only increases the number of surface acidic sites but also enhances the mobility of lattice oxygen through lattice substitution, significantly improving the catalyst's response to NH3 and NO. x Adsorption and activation capabilities.

[0015] 3) Excellent denitrification activity and strong adaptability over a wide temperature window: Through systematic optimization of waste acid types and process conditions, the optimal scheme for titanium dioxide waste acid to be acid-washed at 90 ℃ for 2 h and calcined at 500 ℃ was determined. Experiments show that the catalyst prepared using 30% titanium dioxide waste acid, thanks to the regulation of surface redox properties by synergistic additives, maintains 100% denitrification activity in a wide temperature range of 280–440 ℃, which is significantly better than unmodified red mud and pure acid-modified samples, solving the problem of narrow active temperature range of traditional red mud catalysts.

[0016] 4) Excellent resistance to SO2 poisoning, overcoming industry technical bottlenecks – this is the core advantage of this invention. The introduced in-situ doping synergists (such as titanium and chromium species) significantly enhance the sulfur resistance of the catalyst surface, inhibit excessive deposition of ammonium sulfate / ammonium bisulfate species at active sites, and simultaneously promote the decomposition of surface sulfates. In the anti-poisoning test under a 100 ppm SO2 atmosphere: Primitive Red Mud: Initial NO x The conversion rate was only 70%, dropping to 50% after adding poison, and then returning to 72% after recovery. The catalyst of this invention (modified from 30% titanium dioxide waste acid): initial NO x The conversion rate reaches 100%, and even after poisoning, it maintains a stable conversion rate of 94%, reaching as high as 98% after recovery. The results prove that the catalyst of this invention, through the sulfur-resistant barrier constructed by the synergistic additives, completely solves the problem of easy sulfation and deactivation of red mud-based catalysts, and is extremely suitable for the treatment of sulfur-containing flue gas.

[0017] 5) Waste acid recycling produces an "enrichment and value-added" effect, with broad industrial application prospects. This invention features a simple preparation process, controllable costs, and unique advantages in waste acid recycling. As the number of waste acid recycling cycles increases (5-10 times), the concentration of polyvalent metal cations enriched in the waste acid gradually rises, which in turn enhances the loading of in-situ doping synergistic agents in subsequent batches of catalyst, resulting in improved catalyst performance. This "the more you use it, the better it becomes" characteristic significantly reduces raw material costs and has great value for industrial application. Attached Figure Description

[0018] Figure 1 This is a graph showing the catalytic activity evaluation at different calcination temperatures.

[0019] Figure 2 The graph shows the catalytic activity evaluation for different acid washing times.

[0020] Figure 3 The performance of NH3-SCR at different pickling temperatures. Detailed Implementation

[0021] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that, unless otherwise specified, the embodiments and features described in the present invention can be combined with each other.

[0022] Example 1: Experiment on the preparation of catalysts modified with different types and concentrations of waste acid This embodiment investigates the effects of different types of industrial waste acid and different concentrations of waste acid on the denitrification activity of red mud-based denitrification catalysts under ambient temperature conditions. The core acid washing and calcination basic process parameters were fixed, and the variables were the concentrations of electroplating waste acid, titanium dioxide waste acid, and chemical synthesis waste acid. The specific experimental group parameters are shown in Table 1 below.

[0023] Table 1

[0024] Meanwhile, multiple experimental groups with differentiated processes were set up to investigate the effects of temperature, time, and calcination parameters on catalyst performance. The specific parameters are shown in Table 2 below.

[0025] Table 2

[0026] Taking Example 1.3 (30% titanium dioxide waste acid modified system) as an example, which has the best performance, the specific preparation steps of the catalyst of the present invention are as follows: The raw red mud was pre-treated by drying to remove free moisture. 5g of the dried red mud was accurately weighed and set aside. 30mL of a 30% (w / w) titanium dioxide waste acid solution was measured and thoroughly mixed with the prepared red mud. The mixture was then placed in a constant temperature environment of 90℃ for acid leaching modification for 2 hours. During this process, hydrogen ions in the waste acid selectively dissolved inert components such as sodium and silicon from the red mud lattice, while simultaneously inducing titanium ions associated with the waste acid to migrate to and anchor on the red mud surface, achieving synergistic modification through pore structure etching and in-situ doping. After the acid leaching reaction, the mixture was filtered for solid-liquid separation, and the waste acid solution was recovered for recycling. The resulting solid filter cake was placed in a drying device and dried at a constant temperature for 12 hours to completely remove moisture. Finally, the dried solid sample was placed in a muffle furnace and heated to 500℃ at a uniform heating rate of 2℃ / min, and calcined at that temperature for 2 hours. The calcination process promotes the transformation of amorphous iron species on the surface into the highly active α-Fe2O3 crystalline phase, which then forms a solid solution structure with doped titanium ions, constructing a "Fe-OS-Ti" multi-element active center. After natural cooling, a red mud-based denitrification catalyst modified with 30% titanium dioxide waste acid is obtained.

[0027] Example 2: Application Test Experiment of Catalyst Denitrification Performance This embodiment tests the flue gas denitrification performance of the waste acid-modified red mud-based denitrification catalysts prepared in different experimental groups. The testing device is a fixed-bed reactor, and the specific application and testing steps are as follows: 0.3g of the prepared catalyst sample was precisely loaded into a fixed-bed reaction tube. Before testing, the reaction tube and system were thoroughly purged with high-purity nitrogen to eliminate air impurities. After purging, ammonia, nitric oxide, and oxygen were continuously introduced into the reaction system according to the set ratio to simulate industrial flue gas, with the total gas flow rate controlled at 200ppm. The fixed-bed reaction temperature was adjusted, and a gradient temperature increase test was conducted within the range of 250–500℃ to explore the denitrification activity temperature window of the catalyst. After each reaction stabilized, experimental data were collected and exported. After the test, the residual reaction gas in the tube was purged again with nitrogen until there was no residual waste gas in the system. After the fixed-bed temperature naturally cooled to room temperature, the catalyst sample was removed, completing a single test experiment.

[0028] The denitrification activity of catalysts modified with waste acid of various concentrations was tested under the unified testing conditions described above. The specific performance results are shown in Table 3 below.

[0029] Table 3

[0030] The test results show that, under the same test conditions, red mud-based catalysts modified with industrial waste acid of different concentrations all exhibit certain denitrification performance. Among them, the catalyst modified with 30% concentration of industrial waste acid showed the best performance, and its denitrification activity could be stably maintained at 100% within the optimal temperature range of 280-440℃. This is because the titanium ions in the waste acid at this concentration just reached the optimal doping threshold, forming the richest "Fe-OS-Ti" multi-element active centers with the iron species in the red mud, which greatly enhanced the fluidity of lattice oxygen and was significantly better than the low-concentration (insufficient doping) and high-concentration (excessive etching leading to structural collapse) waste acid-modified samples.

[0031] Example 3: Test Experiment on the Catalyst's Resistance to SO2 Poisoning To verify the industrial application stability and anti-poisoning ability of the modified catalyst of this invention, a SO2 poisoning comparison experiment was conducted in this embodiment. The unmodified original red mud catalyst was used as the control group, and the optimal catalyst modified with 30% titanium dioxide waste acid was used as the experimental group. The changes and recovery performance of catalyst activity were tested under sulfur-containing flue gas conditions. The specific experimental parameters and results are shown in Table 4 below.

[0032] Table 4

[0033] Experimental results show that the unmodified original red mud catalyst has extremely poor resistance to sulfur poisoning, with an initial NO content of [missing information]. xThe conversion rate was only 70%. After introducing 100ppm SO2 poisoning gas, the activity dropped sharply to 50%. After stopping the introduction of SO2, the catalyst activity could only recover slightly to 72%, and it could not restore the initial performance. The irreversible defect of sulfur poisoning was obvious, making it difficult to adapt to the denitrification conditions of sulfur-containing flue gas in industry.

[0034] The red mud-based denitrification catalyst prepared by modifying 30% titanium dioxide waste acid in this invention has significantly improved sulfur resistance, and the initial NO content is reduced. x The conversion rate can reach 100%; under the harsh operating conditions of continuous introduction of 100ppm SO2, it can still maintain an ultra-high stable denitrification conversion rate of 94%; after the SO2 introduction is terminated, the catalyst activity can be quickly restored to 98%, with extremely low activity loss and excellent reversibility.

[0035] Mechanism analysis confirms that the superior sulfur resistance of this invention stems not only from the removal of alkaline impurities and the increase of acidic sites on the surface during the acid washing process, but more importantly, from the synergistic additive (titanium species) introduced through in-situ doping with waste acid. The doped titanium ions alter the electron cloud density on the catalyst surface, constructing an anti-sulfur barrier and effectively inhibiting the deep oxidation of SO2 and sulfate deposition at active sites. Simultaneously, the enhanced lattice oxygen mobility promotes the thermal decomposition and desorption of surface sulfate species, fundamentally overcoming the technical bottleneck of easy sulfation and deactivation of traditional red mud catalysts.

[0036] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely preferred examples and are not intended to limit the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.

Claims

1. A red mud-based denitrification catalyst synergistically modified with industrial waste acid, characterized in that, The red mud-based denitrification catalyst is prepared by synergistic modification of red mud and industrial waste acid; wherein, the red mud is the catalyst matrix material, and the industrial waste acid is the structure regulating component, used to regulate the surface acid-base properties and pore structure of the red mud; in the red mud-based denitrification catalyst, the mass fraction of iron is 10.4% to 13.6%, and the mass fraction of sulfur is greater than 0 and does not exceed 26%.

2. The industrial waste acid-modified red mud-based denitrification catalyst as described in claim 1, characterized in that, The industrial waste acid is one or more of titanium dioxide waste acid, electroplating waste acid, and chemical synthesis waste acid.

3. A method for preparing the industrial waste acid synergistic modification red mud-based denitrification catalyst according to claim 1, characterized in that, The process includes the following steps: using industrial waste acid to acid wash and modify red mud, then separating and recovering the waste acid, and drying and calcining the resulting solid product to obtain the waste acid-modified red mud-based denitrification catalyst.

4. The preparation method of the industrial waste acid synergistic modification red mud-based denitrification catalyst as described in claim 3, characterized in that, The liquid-to-solid ratio of the industrial waste acid to the red mud is 2–6 mL / g.

5. The preparation method of the industrial waste acid synergistic modification red mud-based denitrification catalyst as described in claim 3, characterized in that, The waste acid has a mass fraction of 10–40 wt%.

6. The preparation method of the industrial waste acid synergistic modification red mud-based denitrification catalyst as described in claim 3, characterized in that, The pickling modification temperature is 20–130 °C.

7. The preparation method of the industrial waste acid synergistic modification red mud-based denitrification catalyst as described in claim 3, characterized in that, The pickling modification time is 0.5 to 6 hours.

8. The preparation method of the industrial waste acid synergistic modification red mud-based denitrification catalyst as described in claim 3, characterized in that, The recovered waste acid can be recycled 5 to 10 times.

9. The preparation method of the industrial waste acid synergistic modification red mud-based denitrification catalyst as described in claim 3, characterized in that, The roasting temperature is 300–700 °C.

10. The application of an industrial waste acid-modified red mud-based denitrification catalyst as described in claim 1 or 2, characterized in that, The catalyst is used for flue gas denitrification, and the reaction conditions are as follows: NO volume fraction of 300–1000 ppm, NH3 to NO molar ratio of 0.8–1.2, O2 volume fraction of 1–10%, and mass hourly space velocity of 10,000–60,000 mL·g. - ¹·h - ¹, The reaction temperature is 250–500 °C.

Citation Information

Patent Citations

  • Heteropoly acid doped V2O5-WO3 / TiO2 based medium-low-temperature SCR (selective catalytic reduction) denitrification catalyst

    CN104801349A

  • A red mud SCR catalyst, its preparation method and application

    CN113198445B